THE DIFFERENCE BETWEEN PREGNANCY GYMNASTICS AND PRENATAL YOGA TREATMENT TOWARD PREGNANT MOTHER ANXIOUSNESS GRADE IN THIRD TRIMESTER IN PREGNANT MOTHER CLASS, UNGARAN PUBLIC HEALTH CENTER WORK AREA, SEMARANG REGENCY - Riza Amalia (Jurnal Komunikasi Kesehatan, 2014)
Background : Anxiety is common in pregnant women third trimester. Anxiety affects ofprolonged labor, premature birth, LBW ( Low Birth Weight ). To prevent and reduce theanxiety, the prenatal pregnancy exercise and yoga as an alternative therapy given topregnant women.Purpose : To determine differences in treatment pregnancy gymnastics and prenatalyoga treatment toward pregnant mother anxiousness grade in third trimester inpregnant mother class, Ungaran Public Health Center Work Area.Methods : This study used a quasy experimental with pretest posttest design. Thesampling technique using purposive sampling technique, which amounts to 34 pregnantwomen in the third trimester Ungaran Public Health Center.Results : The results obtained there is a difference in treatment pregnancy gymnsticsand yoga prenatal treatment on the level of anxiety third trimester pregnant women witha Z count ( 3,335 ) > Z table ( 1,96 ) and the p value of 0,001 ( p < 0,05 ). Deltarespondents in the treatment of anxiety pregnancy exercise with mean 11,82; deltarespondents anxiety on treatment with prenatal yoga prenatal yoga mean of 23,18means more effective in reducing anxiety third trimester pregnant women.Conclusion : There is a difference in treatment pregnancy gymnastics and yogaprenatal treatment on the level of anxiety third trimester pregnant women. Pregnancygymnastics can lower the anxiety of 26,5%. While prenatal yoga can lower anxiety by62,3%. This means more effective prenatal yoga lowers levels of anxiety compared withpregnancy gymnastics .